A DFT Study of Structural and Bonding Properties of Complexes Obtained from First-Row Transition Metal Chelation by 3-Alkyl-4-phenylacetylamino-4,5-dihydro-1H-1,2,4-triazol-5-one and Its Derivatives - Hubert Jean Nono; Désiré Bikélé Mama; Julius Numbonui Ghogomu; Elie Younang (Bioinorganic Chemistry and Applications)
Density functional calculations were used to explore the complexation of 3-alkyl-4-phenylacetylamino-4,5-dihydro-1h-1,2,4-triazol-5-one (ADPHT) derivatives by first-row transition metal cations. Neutral ADPHT ligand and mono deprotonated ligands have been used. Geometry optimizations have been performed in gas-phase and solution-phase (water, benzene, and N,N-dimethylformamide (DMF)) with B3LYP/Mixed I (LanL2DZ for metal atom and 6-31+G(d,p) for C, N, O, and H atoms) and with B3LYP/Mixed II (6-31G(d) for metal atom and 6-31+G(d,p) for C, N, O, and H atoms) especially in the gas-phase. Single points have also been carried out at CCSD(T) level. The B3LYP/Mixed I method was used to calculate thermodynamic energies (energies, enthalpies, and Gibb energies) of the formation of the complexes analyzed. The B3LYP/Mixed I complexation energies in the gas phase are therefore compared to those obtained using B3LYP/Mixed II and CCSD(T) calculations. Our results pointed out that the deprotonation of the ligand increases the binding affinity independently of the metal cation used. The topological parameters yielded from Quantum Theory of Atom in Molecules (QTAIM) indicate that metal-ligand bonds are partly covalent. The significant reduction of the proton affinity (PA) observed when passing from ligands to complexes in gas-phase confirms the notable enhancement of antioxidant activities of neutral ligands.